Social Media Use and Preferences in Patients With Inflammatory Bowel Disease. Issue 3 (7th September 2018) - Reich, Jason; Guo, Ling; Groshek, Jacob; Weinberg, Janice; Chen, Wenli; Martin, Christopher; Long, Millie D; Farraye, Francis A
Abstract: Introduction: There has been growing interest in social media use in managing chronic illnesses. The aim of this study was to assess social media usage in a large sample of patients with inflammatory bowel disease (IBD). Methods: We performed a cross-sectional study within the Crohn's and Colitis Foundation's IBD Partners' internet-based cohort. We used bivariate analyses to compare patient characteristics by various factors associated with social media utilization. We used logistic regression models to determine factors independently associated with using social media to obtain IBD-related information. Results: A total of 1960 IBD patients were included. Most respondents reported spending between 30 and 60 minutes on social media sites per day. Thirty-two percent of respondents agreed that social media could be useful for disease management. Most respondents agreed that social media should be used to connect patients with IBD-related organizations and to obtain IBD-related information online. Fifty percent of respondents could not rate the quality of IBD information posted online. Concerns surrounding social media use included privacy/confidentiality and lack of trust of information posted. The most frequently used social media website was Facebook. Thirty-two percent of respondents used social media at least once in the last week to obtain or post IBD-related content. Factors independently associated with social media use for IBD included female gender (odds ratio [OR] 1.43; 95% CI, 1.10–1.87), age (OR 0.99; 95% CI, 0.98–1.00), remission (OR 0.63; 95% CI, 0.50–0.79), and a diagnosis of Crohn's disease (CD) rather than ulcerative colitis (UC) (OR 0.74; 95% CI, 0.58–0.93). Conclusions: Patients with IBD in this cohort expressed a substantial interest in using social media to aid in disease management. Use was higher in younger patients, females, and patients with active disease. Most patients were unsure of the quality of information posted online, which represents opportunities for clinicians to guide patients to appropriate resources.